In the Refractory Hypertension "Labyrinth". Focus on Primary Hyperaldosteronism - O. V. Tsygankova; T. I. Batluk; L. D. Latyntseva; E. V. Akhmerova; N. M. Akhmedzhanov (Столичная издательская компания, 2020)
Primary hyperaldosteronism is an existence of a functional autonomous source with increased aldosterone production (full or partial) in relation to the renin-angiotensin system. Increased production of aldosterone by the adrenal cortex is the most common form of a secondary hypertension despite the low attention of internists to the problem. The success of a treatment and a prognosis of these patients depend on correct choice of screening (aldosterone/renin ratio) and clarifying diagnostic methods. There are clear algorithms for conducting these tests in accordance with Russian and International recommendations in the respective groups of patients. The purpose of this case report is to demonstrate the long way to diagnosis of primary hyperaldosteronism in a young patient with refractory hypertension, right adrenal adenoma, and clinical (convulsions, weakness) and laboratory signs of hypokalemia. It should not only have made the diagnosis easy, but it could have also absolutely justified the surgical tactics. Unfortunately, the final verification of the disease by carrying out a saline test was accomplished 13 years after the debut of hypertension and 10 years after the primary visualization of the adrenal adenoma.